PEMBUATAN SIRUP UBI JALAR UNGU (Ipomea batatas L.) DENGAN PENAMBAHAN SARI LEMON (Citrus limon L.) - Chairunnisa Saragih; Netti Herawati; Raswen efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to get formulations best of syrup purple sweet potato with additional lime extract in accordance with SNI.Study was conducted experimentally used Complete Design Random (CDR) with four treatments and four replications is SU1 (puree purple sweet potato 90% : lime extract 10%), SU2 (puree purple sweet potato 85% : lime extract 15%), SU3 (pureepurple sweet potato 80% : lime extract 20%) , SU4 (puree purple sweet potato 75% : lime extract 25%). The value of observation were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s New Multilt Range Test (DNMRT) on 5% level.The result showed that the ratio puree purple sweet potato with lemon to making syrup influential real against degrees acidity (pH), viscosity, sucrose, total solids dissolved and assessment sensory.The best treatment syrup was SU1with pH 4,64, sucrose 65,07%, viscosity 116,78 cP, total solid dissolved 65,43 °brix and organoleptic scores of SU1are 3,80 (colour), 3,40 (flavour), 3,42 (taste), 3,88 (sweet of taste) and comprehersive score (3,61). Key words : syrup, purple sweet potato, lime